Future and Contemrorary Conditions of Nature Pastures in South Kazakhstan Region (Experimental biology, 2015)
In the paper it was presented data about the current state of pastures and restore ways of South Kazakhstan, as well as a livestock farms with the use of an innovative technologies. In market conditions the improving of the quality and the increasing of the number of livestock only by increasing of the area of grassland lead to new problems. Therefore, these problems in animal husbandry to increase the number of livestock, the improvement of quality should be made considering the maintaining of balance between use and conservation of grasslands. For this need to introduce innovative technologies based on the establishment of livestock arms and recovery of grassland. The organization of cultural pastures and and their rational use will increase the performance of desert and semidesert grassland in 3-4 times, and thereby it will give the opportunity to provide the need for fodder production fully.
Keywords: pastures; animal breeding; grazing land